Zinc transporter LIV1: A promising cell surface target for triple negative breast cancer. Issue 11 (1st October 2022) - Saravanan, Roshni; Balasubramanian, Vaishnavi; Swaroop Balamurugan, Srikanth Swamy; Ezhil, Inemai; Afnaan, Zeba; John, Jisha; Sundaram, Sandhya; Gouthaman, Shanmugasundaram; Pakala, Suresh B.; Rayala, Suresh Kumar; Venkatraman, Ganesh
Abstract: Breast cancer is one of the leading causes contributing to the global cancer burden. The triple negative breast cancer (TNBC) molecular subtype accounts for the most aggressive type. Despite progression in therapeutic options and prognosis in breast cancer treatment options, there remains a high rate of distant relapse. With advancements in understanding the role of zinc and zinc carriers in the prognosis and treatment of the disease, the scope of precision treatment/targeted therapy has been expanded. Zinc levels and zinc transporters play a vital role in maintaining cellular homeostasis, tumor surveillance, apoptosis, and immune function. This review focuses on the zinc transporter, LIV1, as an essential target for breast cancer prognosis and emerging treatment options. Previous studies give an insight into the role of LIV1 in fulfilling the most important hallmarks of cancer such as apoptosis, metastasis, invasion, and evading the immune system. Normal tissue expression of LIV1 is limited. Higher expression of LIV1 has been linked to Epithelial‐Mesenchymal Transition, histological grade of cancer, and early node metastasis. LIV1 was found to be one of the attractive targets in the therapeutic hunt for TNBCs. TNBCs are an immunogenic breast cancer subtype. As zinc transporters are known to serve as the metabolic gatekeepers of immune cells, this review bridges tumor infiltrating lymphocytes, TNBC and LIV1. In addition, the suitability of LIV1 as an antibody‐drug conjugate (Seattle genetics [SGN]‐LIV1A) target in TNBC, represents a promising strategy for patients. Early clinical trial results reveal that this novel agent reduces tumor burden by inducing mitotic arrest, immunomodulation, and immunogenic cell death, warranting further investigation of SGN‐LIV1A in combination with immuno‐oncology agents. Priming the patient's immune response in combination with SGN‐LIV1A could eventually change the landscape for the TNBC patient population.